Multirate Signal Processing for Communication Systems - Harris, Fred (River Publishers series in signal, image and speech processing., 2021)
Multirate signal processing can improve systemperformance and reduce costs in applications ranging from laboratoryinstruments, cable modems, wireless systems, satellites, Radar, Sonar, andconsumer entertainment products. This second edition continues to offer asystematic, clear, and intuitive introduction to multirate signal processingfor working engineers and system designers. Significant new material and freshconcepts, including Green signal processing techniques have been introduced.